FOTO POTRET KELUARGA DENGAN CAHAYA AVAILABLE LIGHT - Adnyana, I Kadek Dwi Rahma; Candrayana, Ida Bagus; Bratayadnya, Putu Agus (Retina Jurnal Fotografi, 2022)
Abstract This study discusses Family Portrait Photos with Available Light. Family photos are very important. This is because family photos are one of the reminders of memories with father, mother, children, and siblings when they are together at every moment. Available light or natural light according to the author is the most important light in any shooting process, because natural light without being artificial and without the addition of flash has a natural impression. The formulation of the problem in this study discusses how to visualize family portrait photos with available light and how to interact and work in the real world of work. Source studies used in this research are several books, journals and articles related to research problems such as the use of available light, photo-taking techniques and the world of commercial photo work. The theoretical basis used is aesthetic theory as the basis for studying the problem. The implementation method carried out during the research process is the method of observation, interviews, documentation of the results of work practices and several data sources used, namely primary and secondary data. This research is presented in the form of narrative sentences in the form of a thesis. The results of this study indicate that available light is the most important light for outdoor shooting, but in shooting using available light it is necessary to consider time and weather in order to get good lighting in shooting.